Breed differences in olfactory performance of dogs - Attila Salamon; Ádám Miklósi; László Róbert Zsiros; Tímea Kovács; Enikő Kubinyi; Attila Andics; Márta Gácsi (Scientific Reports)
Abstract Most studies on dogs’ olfactory performance focused only on some individuals pre-trained for a task or on specially selected/trained detection dogs. Here, using the Natural Detection Task (NDT) that does not require training, we assessed the effect of several potential factors on the performance of a large sample of dogs (N = 527/tested, 484/analysed). Olfactory success was associated with breeds, but breed groups (selected for olfaction, cooperation, or both) were proven non-relevant, suggesting that breed-specific traits are more influential than functional breed group characteristics. Border collies, selected for herding, reached higher success levels than golden retrievers, Hungarian/German vizslas and basset/bloodhounds, selected for hunting/olfaction tasks. Beagles found the hidden food quicker than border collies, basset/bloodhounds, golden retrievers, Labradors, and cocker spaniels. Dogs with higher Responsiveness to training personality scores were more successful, while higher training level linked to slower successful search. Activity/Excitability scores, attention-deficit/hyperactivity disorder scores, and owners’ rewarding style were not associated with performance. Overall, large within-breed/breed-group variabilities reflect complex interactions between genetic and environmental factors influencing performance. Given the complex nature of life-like detection tasks, the NDT may provide more information about dogs’ olfactory ability than on their potential effectiveness in detection work.